Digital Transformation and MSME Well-being: The Mediating Role of Digital Transaction Security - Novi Primita Sari; Sri Budi Cantika Yuli (Global Research Collaboration, 2026)
This study analyzes the relationship between Digital Transformation and MSME Welfare with Digital Transaction Security as a mediating variable. A quantitative approach was used through a survey of 150 MSME actors in Malang Regency, Indonesia, who have utilized digital technology in their business activities. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that Digital Transformation had a positive effect on MSME Welfare (β = 0.298; p = 0.002) and Digital Transaction Security (β = 0.611; p < 0.001). Digital Transaction Security also had a positive effect on MSME Welfare (β = 0.541; p < 0.001). Mediation analysis proved that Digital Transaction Security partially mediates the relationship between Digital Transformation and MSME Welfare (β = 0.330; t = 5.701; p < 0.001). The model demonstrated good explanatory power (R² = 0.373 and 0.592) and high predictive relevance (Q² = 0.744). These findings underscore the importance of strengthening transaction security, digital literacy, and institutional support to improve MSME welfare through digital transformation.